[OA057] Comparative dose planning for Ru-106 brachytherapy and proton therapy for choroidal melanomas. (August 2018) - Espensen, Charlotte; Fog, Lotte; Thariat, Juliette; Herault, Joel; Aznar, Marianne; Maschi, Celia; Caujolle, Jean-Pierre; Kiilgaard, Jens Folke; Appelt, Ane
Abstract : Purpose: Eye-preservation using brachytherapy (BT) and proton therapy (PT) are commonly used as primary treatments for uveal melanomas (UM). Choice of modality generally depends on local availability rather than direct assessment of the two techniques. We conducted a comparative dose planning study, estimating biologically effective doses (BED) to the tumour, macula and optic nerve head (ONH). Methods: We retrospectively included 70 patients with primary UM: 35 treated with Ruthenium-106 (Ru-106) BT, and 35 who underwent PT. Only PT patients whose tumour was small enough to be treatable by BT were included. Prescriptions were 100 Gy (continuously delivered in a single session) for BT and 52 Gy (in 4 fractions) for PT to the entire tumour. Both planning techniques aimed to minimize doses to macula and ONH without compromising tumour coverage. Dual image-guided planning with 3D dose calculation was carried out for each patient. Dose volume histograms for tumour, macula, and ONH were extracted. BED was calculated using well-established models: Gagne et al. (Med Phys, 2012) for BT and Holloway and Dale (Br J Radiol, 2013) for PT, correcting for fractionation effects, overall treatment time and relative biological effectiveness. Wilcoxon signed-rank test was used to evaluate differences in BED. Results: Minimum tumour BEDs (BED99%) were larger for BT with median 159 Gy (interquartile range (IQR): 149–168) compared to 128 Gy (128–128) for PT. The median difference was 31 Gy (21–41) with p < 0.0001. Median macula BED50% was 72 Gy (22–587) for BT compared to 155 Gy (0–374) for PT. However, the median of the individual patient difference was 23 Gy (1–248, p  = 0.0002), favoring PT. Median ONH BED50% was 46 Gy (15–291) for BT compared to 3 Gy (0–525) for PT but the difference was not statistically significant ( p  = 0.1). PT spared the macula for smaller tumours < 2 mm from the macula, while the ONH received less dose with BT in juxtapapillary cases. Conclusions: Ru-106 brachytherapy delivered larger tumour doses, larger macula doses, and comparable optic nerve head doses compared to proton therapy. Large individual variations were seen, emphasizing the need for prospective comparative planning to guide the choice of treatment modality.